Versorgungs-Report Leitlinien Evidenz für die Praxis - Günster, Christian; Klauber, Jürgen; Klemperer, David; Nothacker, Monika; Robra, Bernt-Peter; Schmuker, Caroline (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2023)
This issue of the Healthcare Report focuses on the importance of medical guidelines in healthcare. Guidelines provide the treating person with diagnostic and therapeutic recommendations. They are developed according to systematic and evidence-based criteria and aim to improve the quality of care for patients. As patient guidelines, they influence the health literacy of the population. Their implementation in everyday care is challenging. The expert contributions in the care report deal extensively with the practice of guidelines. They describe methods and procedures for the creation of trustworthy guidelines and their evaluation. They report on the results of empirical studies on the implementation of guideline recommendations in real care and present practice-oriented care structures and concrete contract models to promote the use of guidelines. The "Data and Analysis" part reports on the frequency of illnesses and treatments in Germany based on AOK billing data and takes a look at the effects of the pandemic. Further data on treatment frequencies for more than 1,500 diseases are available at www.mwv-open.de.